Religious Coping, Medication Adherence and Quality of Life for Diabetes Mellitus Patients - Made Mahaguna Putra; Kadek Siki Mariani; Ni Nyoman Ari Ratnadi (Universitas Airlangga, 2021)
Introduction: Diabetes mellitus is a major public health issue particularly in the elderly. Religion may affect the Quality of Life in such patients, mediated by factors such as religious coping and medication adherence. This study aimed to investigate the impact of religious coping and medication adherence on quality of life.Method: Diabetes mellitus is a major public health issue particularly in the elderly. Religion may affect the Quality of Life in such patients, mediated by factors such as religious coping and medication adherence. This study aimed to investigate the impact of religious coping and medication adherence on quality of life.Result: there is a significant relationship between Religious Coping and adherence to treatment in Diabetes Mellitus patients with a value of r = 0.266 (p = 0.00) and quality of life (r = 0.216; p = 0.00).Conclusion: Religious coping has an important influence and relationship on treatment adherence to diabetes mellitus sufferers and can provide motivation for sufferers in carrying out medication.